World scientific production on covid-19: Analysis of the period February-march, 2020 - Arias-Chávez, D. (2020)
The objective of the study is to characterize, using bibliometric indicators, the world scientific production on COVID-19 in the field of scientific publications in all languages between the months of February and March of the year 2020. A descriptive-retrospective bibliometric study was carried out, covering the world’s first scientific papers on the COVID-19. Using the Google Academic database, the bibliometric indicators were calculated using the Publish or Perish Software v. 7.19, filtering 1000 results, which yielded a total of 1822 citations, 1.82 and 700.09 citations per article and citations by author respectively. The publications have an h index of 17, a g index of 31 and an e index of 22.05. Finally, the AW index was 42.67 and the AWCR was 84.26. The 3610 authors of the articles analyzed work mostly individually (27.30%), which generates a collaboration index of 3.61. The databases Medrixiv, org and The Lancet stand out, the latter being the most important journal. These results show that the scientific production related to the worldwide COVID-19 is in a constant and dizzying growth.